2004
DOI: 10.1056/nejmoa040186
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Replacement with a Total Artificial Heart as a Bridge to Transplantation

Abstract: Implantation of the total artificial heart improved the rate of survival to cardiac transplantation and survival after transplantation. This device prevents death in critically ill patients who have irreversible biventricular failure and are candidates for cardiac transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
218
1
12

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 469 publications
(232 citation statements)
references
References 11 publications
1
218
1
12
Order By: Relevance
“…Despite such disheartening results, some surgeons have continued to use the device with some degree of success. Jack Copeland, for example, has demonstrated that using an artifi cial heart as a bridge to cardiac transplantation can result in signifi cant increases in survival time to transplantation and improved survival after transplantation (25). Kolff , in his remaining years, maintained his enthusiasm for the total artifi cial heart and felt that its ultimate success only required better design and better medical management.…”
Section: The Total Artificial Heartmentioning
confidence: 99%
“…Despite such disheartening results, some surgeons have continued to use the device with some degree of success. Jack Copeland, for example, has demonstrated that using an artifi cial heart as a bridge to cardiac transplantation can result in signifi cant increases in survival time to transplantation and improved survival after transplantation (25). Kolff , in his remaining years, maintained his enthusiasm for the total artifi cial heart and felt that its ultimate success only required better design and better medical management.…”
Section: The Total Artificial Heartmentioning
confidence: 99%
“…Die Implantation eines CardioWest kann u. a. in Fällen von ausgedehnten akuten Myokardinfarkten (AMI), Tumoren im Herzen oder auch ausgedehnten Thromben in beiden Herzkammern in Erwägung gezogen werden. Copeland et al berichtete in einer multizentrischen Studie an 81 BTT-Patienten von einem Einjahresüberleben von 79% sowie einem Einjahresüberleben nach HTx und vorangegangener CardioWestUnterstützung von 86% [28]. Morschuis und Kollegen berichteten über 5 Patienten mit ausgedehntem AMI, welche mit einem TAH-CardioWest gerettet wurden.…”
Section: Introductionunclassified
“…This is best summarised in a meta-analysis by Cheng et al, with a conclusion that despite better haemodynamic profile mortality does not decrease significantly [45]. However, these devices may be a bridge to heart transplantation or -if the donor is lacking -to total artificial heart implantation and staged transplantation with an excellent long-term survival [46][47][48].…”
Section: Novel Devices and Areas Of Future Researchmentioning
confidence: 99%